2004
DOI: 10.3141/1872-09
|View full text |Cite
|
Sign up to set email alerts
|

Market Segmentation Approach to Mode Choice and Ferry Ridership Forecasting

Abstract: The San Francisco Bay Area Water Transit Authority is evaluating expanded ferry service, as required by the California legislature. Predicting ferry ridership has historically been difficult because water-transit riders often choose their travel mode based on factors other than travel time and cost. Most forecast models place a premium on time and cost and ignore other traveler attitudes. Structural equation modeling was used to identify simultaneously travel behavior and the causal relationships between a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Travel behavior studies [10,[48][49][50] have shown that PT users' socio-demographics and trip characteristics have an effect on their travel behavior. Guo and Wilson [7] discussed that frequent riders tend to be more familiar with the PT network and services and therefore perceive transfers to be less onerous than infrequent riders.…”
Section: Hypothesismentioning
confidence: 99%
“…Travel behavior studies [10,[48][49][50] have shown that PT users' socio-demographics and trip characteristics have an effect on their travel behavior. Guo and Wilson [7] discussed that frequent riders tend to be more familiar with the PT network and services and therefore perceive transfers to be less onerous than infrequent riders.…”
Section: Hypothesismentioning
confidence: 99%
“…The structural equation modeling (SEM) approach is one of the most appropriate techniques for identifying latent variables and analyzing the correlational relationship among them, since it combines the advantages of confirmatory factor analysis and path analysis (multiple regression), which can test the linear causal relationship among variables and assess the hypothetical model with both manifest and latent variables. SEM has been widely applied in various transportation fields, including travel behavior and demand (e.g., [20][21][22][23][24][25][26][27][28][29]), mode choice (e.g., [30][31][32][33]), service quality (e.g., [34][35][36]), and transport safety (e.g., [37,38]) during recent decades. The SEM approach possesses several technologic advantages over other statistical methods.…”
Section: Confirmatory Factor Analysis and Structural Equation Modelingmentioning
confidence: 99%
“…Some literature suggest that where customers are informed about environmental stewardship implications, ridership or cargo volume on a cleaner vessel could be positively affected; these factors are being considered in marketing efforts for expanded ferry service. 39 If the physical attributes of an alternative reduce vessel capacity, then there may be some negative revenue impacts.…”
Section: Alternatives Identificationmentioning
confidence: 99%